1989
DOI: 10.1038/339309a0
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal dominant disorder with multiple deletions of mitochondrial DNA starting at the D-loop region

Abstract: Deletions of muscle mitochondrial DNA (mtDNA) have recently been found in patients with mitochondrial myopathy. However, as most of the described cases were sporadic, and individual deletions involved different portions of mtDNA, the mechanism(s) producing the molecular lesions, as well as their mode of transmission, remain unclear. By studying families with mtDNA heteroplasmy, valuable information can be obtained about the role of inheritable factors in the pathogenesis of these disorders. We have studied fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
272
0
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 571 publications
(290 citation statements)
references
References 21 publications
12
272
0
6
Order By: Relevance
“…It is demonstrated that the disorder of mtDNA can be induced by the defects of nuclear DNA [46]. Another putative mechanism is associated with reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that the disorder of mtDNA can be induced by the defects of nuclear DNA [46]. Another putative mechanism is associated with reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, Zeviani and colleagues described autosomal dominant progressive external ophthalmoplegia (adPEO) with multiple mtDNA deletion, the first of several diseases attributed to defects of nuclear DNA leading to the disorder of mtDNA (Zeviani et al, 1989). Mutations in the mitochondrial proteins adenine nucleotide translocator 1 (ANT1) (Kaukonen et al), Twinkle (Spelbrink et al) and polymerase γ (Van Goethem et al) have been found to cause autosomal dominant progressive external ophthalmoplegia with multiple deletion of mtDNA.…”
Section: Causes For Mtdna Depletion and Deletionmentioning
confidence: 99%
“…2 Severe cases of mitochondrial myopathy can present with progressive external ophthalmoplegia (PEO), caused by paralysis of the extraocular eye muscles. 3 One of the best characterized causes of mitochondrial PEO is mutations in the nuclear DNA (nDNA)-encoded gene for the heart-muscle isoform of the adenine nucleotide translocator (Ant1) gene. 4 The ANTs export ATP generated by OXPHOS out across the mitochondrial inner membrane in exchange for cytosolic ADP, and thus are the main modulators of energy flux in the aerobic cell.…”
Section: Introductionmentioning
confidence: 99%